Challenges facing the South African nursing profession - Marie Poggenpoel; Marie Muller (AOSIS, 1996)
The purpose of this article is to describe the results of a study that was conducted to identify challenges facing the nursing profession in a post-apartheid South Africa. Opsomming Die doel van hierdie artikel is om die resultate te beskryf van 'n studie wat onderneem is om uitdagings te identifiseer wat die Suid-Afrikaanse verpleegberoep in die gesig staan. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.